(untitled) (Veterinary Science, 2017)
EBL is a disease of adult cattle caused by the retrovirus, bovine leukemia. It can manifest: aleukemic an asymptomatic form, with a normal number of B lymphocytes in the blood; a form of permanent lymphocytosis, with an increase in the number of B lymphocytes and finally a lymphoproliferative tumor presentation in the form of lymphosarcoma. The alleles of the genes of the Bovine Major Histocompatibility Complex (BoLA) have been associated with resistance and susceptibility to infectious diseases. The overall objective of this study was to associate polymorphisms of the BoLA-DRB3.2 gene, defined by the technique of polymerase chain reaction technique and polymorphisms length of the restriction fragment (PCR-RFLP), with resistance / susceptibility to leucosis in Holstein cows of La Pampa. It relied on a case/control design, for which blood samples were taken to 150 animals in 3 opportunities with intervals of three months each. The case group comprised animals that were positive in the immunodiffusion agar animals test (DIDA) and whose blood lymphocyte count was ≥ 10.000 linf/μl and the control group included cows that ware negative for DIDA and present < 10.000 linf/μl of blood. Fisher’s Exact test and Odds Ratio (OR) of Woolf-Haldane were used to study the association between lymphocyte count and DIDA results with allelic variants. In 82 animals genotyped by PCR-RFLP, the DRB3.2*22 allele showed an OR = 5.332 (p = 0.0138) and DRB3.2*11 allele had a OR value of 0.11 (p=0.001) and were the most frequent in the control group and in the case group, respectively. These results would showed DRB3.2*22 allele and DRB3.2*11 allele a high risk of having leucosis (susceptibility) and low risk to suffer (resistance) respectively. The analysis of the relationship between alleles of the BoLA and resistance/susceptibility to leucosis could be improved with deep research on family lineages of dairy cows.